Violent crime motivated by war-related hate: concepts, signs, development trends - V. V. Sokurenko (Bulletin of Kharkiv National University of Internal Affairs)
The article substantiates the need to study violent crime motivated by hatred related to the war as a separate criminological category in view of the ongoing armed conflict on the territory of Ukraine, the annexation of part of its territories and open calls by the Russian authorities to destroy the Ukrainian nation, incite hatred to everything that identifies Ukraine as a sovereign independent state.